MAKNA SIMBOL BUSANA TARI SIGAL DALAM UPACARA GAWIA SOWA’K DI KECAMATAN JAGOI BABANG KABUPATEN BENGKAYANG PROVINSI KALIMANTAN BARAT - Mega Diah Rosanti; Imma Fretisari; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to describe the meaning of the Sigal dance clothing symbol in the Sowa'k Gawia Ceremony in Jagoi Babang, Bengkayang Regency, West Kalimantan. The researched problem was about the meaning of color symbols, shape motifs and the use of Sigal dance attire in the Gawia Sowa'k Ceremony Jagoi Babang district, Bengkayang regency West Kalimantan.The research method was the descriptive method with a qualitative form using the semiotic approach. The sources of the data were the results of interviews, field notes and documentation of the informants namely Ginop, Mihek, and Gabriel Armando. The techniques of data validity used triangulation and the techniques of data analysis were systematically collected and analyzed. The findings showed that there were fern motifs that symbolically meant humans need to bond with another. They must work unitedly and need social connectedness to protect each other. A symbol of shoot bamboo meant a guide to the path of truth. The lower line motif with an upward taper shape and the upper line with a downward taper indicated the symbol of men who dares to respectfully carry the responsibility and obligations as Dayak Jagoi tribesmen. The symbol of color in this dress meant a cycle of human life. Keywords : Symbolic meaning, Clothing dance, Sigal dance, Gawai Sowa’k Ceremony